Klein werk : de Opuscula hebraea graeca latina et gallica, prosaica et metrica van Anna Maria van Schurman (1607-1678) - Van Beek, Pieta (Stellenbosch : Stellenbosch University, 2012)
Thesis (DPhil)--Stellenbosch University, 1997.